The relationship between parenting style and peer pressure on at-risk behavior among adolescents - Syairah Aimi Shamsul Baharin,; Abdul Rahman Ahmad Badayai, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Parenting style and peer pressure are one of the important elements for adolescents. However, there are increment in the number of adolescents involved that with smoking behavior.The purpose of this study was to identify the main causes and predictors of the smoking behavior especially among adolescents. The parenting style and peer influence were used as the independent variables for this at-risk behaviors. This study was a cross-sectional study. A total of 197 respondents were selected from Form 6 students at several Form 6 centers in Seremban, Negeri Sembilan. The majority of the respondents were male, of whom 122 were (61.9%) and 75 (38.1%) were female and were involved in cigarette use. The study used Parental Authority Questionnaire, Questionnaire-Revised Peer Pressure and Smoking Urge-Brief that have been translated into Malay language to measure all the variables that exist in the study. Questionnaire was distribute using online method by Google Form software and Whats-app applications. The results show that there is a significant relationship between parenting style and peer influence on cigarette use among adolescents. In addition, this study also found that there were differences in the level of use of cigarettes by gender and that there were differences in parenting style by gender. Therefore, parenting style and peer influence play an important role in adolescent involvement with smoking behavior.